Effect of individual environmental heat-stress variables on training and recovery in professional team sport - O`Connor, F. K.; Stern, S. E.; Doering, T. M.; Minett, G. M.; Reaburn, P. R.; Bartlett, J. D.; Coffey, V. G. (International Journal of Sports Physiology and Performance, 2020)
Context: Exercise in hot environments increases body temperature and thermoregulatory strain. However, little is known regarding the magnitude of effect that ambient temperature (Ta), relative humidity (RH), and solar radiation individually have on team-sport athletes. Purpose: To determine the effect of these individual heat-stress variables on team-sport training performance and recovery. Methods: Professional Australian Rules Football players (N = 45) undertook 8-wk preseason training producing a total of 579 outdoor field-based observations with Ta, RH, and solar radiation recorded at every training session. External load (distance covered, in m/min; percentage high-speed running [%HSR] >14.4 km/h) was collected via a global positioning system. Internal load (ratings of perceived exertion and heart rate) and recovery (subjective ratings of well-being and heart-rate variability [root mean square of the successive differences]) were monitored throughout the training period. Mixed-effects linear models analyzed relationships between variables using standardized regression coefficients. Results: Increased solar-radiation exposure was associated with reduced distance covered (-19.7 m/min, P < .001), %HSR (-10%, P < .001) during training and rMSSD 48 h posttraining (-16.9 ms, P = .019). Greater RH was associated with decreased %HSR (-3.4%, P = .010) but increased percentage duration >85% HRmax (3.9%, P < .001), ratings of perceived exertion (1.8 AU, P < .001), and self-reported stress 24 h posttraining (-0.11 AU, P = .002). In contrast, higher Ta was associated with increased distance covered (19.7 m/min, P < .001) and %HSR (3.5%, P = .005). Conclusions: The authors show the importance of considering the individual factors contributing to thermal load in isolation for team-sport athletes and that solar radiation and RH reduce work capacity during team-sport training and have the potential to slow recovery between sessions.